Greed: Taking a deadly sin to the lab - Michael Razen; Matthias Stefan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
The term greed has become very popular in the public debate. It is regularly argued, for instance, that greed is one of the deep rooted reasons for the financial crisis, numerous incidents of fraud and growing inequalities in wealth. Despite its prominent role in the current debates, however, empirical research on greed is rather sparse. We argue that the major impediment for empirical studies is the difficulty to distinguish greed from selfishness. To overcome this methodological problem, we propose a modified version of the classic dictator game which allows us to unambiguously distinguish greed from other forms of self-centered behavior in an experimental environment. Building on the notion of greed as a selfish and excessive desire for more than is needed, we introduce an artificial point of material satiation. We find that greed is indeed observable under laboratory conditions and that it is even one of the predominant behavioral motives. We also find that feelings of entitlement significantly increase the frequency of greedy behavior. Further, our results indicate that feelings of social obligation have no impact on the proportion of greedy behavior.
Keywords: 330; experimental economics; greed; entitlement